Return to training in the COVID‐19 era: The physiological effects of face masks during exercise. (30th September 2020) - Epstein, Danny; Korytny, Alexander; Isenberg, Yoni; Marcusohn, Erez; Zukermann, Robert; Bishop, Boaz; Minha, Sa'ar; Raz, Aeyal; Miller, Asaf
Abstract : COVID‐19 outbreak has a profound impact on almost every aspect of life. Universal masking is recommended as a means of source control. Routinely exercising in a safe environment is an important strategy for healthy living during this crisis. As sports clubs and public spaces may serve a source of viral transmission, masking may become an integral part of physical activity. This study aimed to assess the physiological effects of wearing surgical masks and N95 respirators during short‐term strenuous workout. This was a multiple cross‐over trial of healthy volunteers. Using a standard cycle ergometry ramp protocol, each subject performed a maximal exercise test without a mask, with a surgical mask, and with an N95 respirator. Physiological parameters and time to exhaustion were compared. Each subject served his own control. Sixteen male volunteers (mean age and BMI of 34 ± 4 years and 28.72 ± 3.78 kg/m 2, respectively) completed the protocol. Heart rate, respiratory rate, blood pressure, oxygen saturation, and time to exhaustion did not differ significantly. Exercising with N95 mask was associated with a significant increase in end‐tidal carbon dioxide (EtCO2 ) levels. The differences were more prominent as the load increased, reaching 8 mm Hg at exhaustion (none vs N95, P  = .001). In conclusion, in healthy subjects, short‐term moderate‐strenuous aerobic physical activity with a mask is feasible, safe, and associated with only minor changes in physiological parameters, particularly a mild increase in EtCO2 . Subjects suffering from lung diseases should have a cautious evaluation before attempting physical activity with any mask.